2018
DOI: 10.1112/s0010437x18007297
|View full text |Cite
|
Sign up to set email alerts
|

Four-fold Massey products in Galois cohomology

Abstract: In this paper, we develop a new necessary and sufficient condition for the vanishing of 4-Massey products of elements in the mod-2 Galois cohomology of a field. This new description allows us to define a splitting variety for 4-Massey products, which is shown in the Appendix to satisfy a local-to-global principle over number fields. As a consequence, we prove that, for a number field, all such 4-Massey products vanish whenever they are defined. This provides new explicit restrictions on the structure of absolu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…On the other hand, Harpaz and Wittenberg show in [HaW19] that the above property of 3-fold Massey products does not hold for F = Q and m = 8, so the assumption about roots of unity cannot be removed in general. Following [GMTW18], [GM19], they prove the above fact for general n-fold Massey products, n ≥ 3, in the case where F is a number field and m = p is prime. We refer to [PS16] for related results.…”
mentioning
confidence: 89%
“…On the other hand, Harpaz and Wittenberg show in [HaW19] that the above property of 3-fold Massey products does not hold for F = Q and m = 8, so the assumption about roots of unity cannot be removed in general. Following [GMTW18], [GM19], they prove the above fact for general n-fold Massey products, n ≥ 3, in the case where F is a number field and m = p is prime. We refer to [PS16] for related results.…”
mentioning
confidence: 89%
“…[34]) it can be shown that the non-trivial element of B ω (V )/Br 0 (V ) is in fact locally constant and yields a nontrivial obstruction to the Hasse principle (see [GMT18,Example A.15]). We note that this is by no means a contradiction to Theorem 5.1: indeed, an obstruction coming from a locally constant Brauer class means that the homomorphism α : Γ k −→ A = U/U 1 does not lift to U/U 3 = U/Z, and hence the relevant Massey product is not defined.…”
Section: More Brauer Group Computationsmentioning
confidence: 99%
“…The claim in the general non-trivial case was proven in [MT17b, Theorem 4.3], using local duality. (3) When k is a number field, n = 4 and p = 2 [GMT18].…”
Section: Introductionmentioning
confidence: 99%
“…But how does one look for those properties that distinguish absolute p-Galois groups from the broader class of pro-p groups? There are several research agendas that aim to answer this question using a number of different techniques, including the study of Massey products (see [39,50,60,84,92,93,94,117,118,120]) and the Koszulity of Galois cohomology (see [82,83,102]).…”
Section: Introductionmentioning
confidence: 99%